2020
DOI: 10.1108/jfmpc-04-2019-0031
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy model for assessing delays in Egyptian residential projects

Abstract: Purpose Construction delays are a common problem in the Egyptian construction industry. Frequent delays in a project can lead to disputes and litigation. This paper aims to study and analyze the causes of construction delays. Design/methodology/approach This research identifies delay causes in residential projects in Egypt and analyzes these causes with the relative importance index method. The feedback of construction experts was obtained through interviews. Subsequently, a questionnaire survey was prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…However, the study only categorized causes in certain groups and identified that equipment, design, contractor, material, and contract are the main categories that generate delays in construction projects. El-Rasas T., Marzouk M. [16] found out that improper planning and delay in payments are ranked first in causing delay in residential projects in Egypt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study only categorized causes in certain groups and identified that equipment, design, contractor, material, and contract are the main categories that generate delays in construction projects. El-Rasas T., Marzouk M. [16] found out that improper planning and delay in payments are ranked first in causing delay in residential projects in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was conducted using fuzzy logic and the relative importance index. Inadequate experience from the contractor, delay in payments, and ineffective planning were the top-ranked parameters [16]. Gebrehiwet T., Luo H. [17] used the correlation coefficient and RII to analyze the causes of delay before the construction stage, during, post-construction stage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Charles, et al, [40], exploring critical road project delay factors in Ghana and grouped them into four main classes which are; client, consultant, contractor, and supplier related causes. A study aims to analyze the causes of construction delays in Egyptian residential projects by Tarek & Mohamed, [41], explored and classified the important factors leading to delay in delivery time into eight groups. The main classification of the major causes of delay in Egyptian residential projects are; owner, consultant, contractor, material, labor, equipment, project, and external related factors.…”
Section: Causes Of Delaymentioning
confidence: 99%
“…Also, the studies in which the factors causing delay in construction were collected and identified from [35,50,3,34,36,51,37,52,32,53]. Furthermore, [5,33,14,38,39,54,38,40,41], were reviewed to collect the main and sub-factors of causing time overrun in construction projects. In general, in this review, an inclusive category on the causes of construction delay was identified after the detailed review of the published articles.…”
Section: Causes Of Delaymentioning
confidence: 99%
“…Some scholars developed models and frameworks on factors concerning construction project delays. In 2020, El-Rasas and Marzouk [ 27 ] analysed the causes of residential construction project delays and developed a fuzzy model to determine the probability of delay. Elhusseiny, Nosair [ 28 ] developed a systemic processing framework in which the most influential delay factors for Egyptian construction projects were slow decision making, changes in the scope of work and payment delays.…”
Section: Introductionmentioning
confidence: 99%